ANALISIS PERSEDIAAN BAHAN BAKU DALAM MENUNJANG PRODUKSI PADA USAHA MARTABAK ALIM KOTA BENGKULU - Ida Ayu Made; Wagini Wagini (UNIVED Press, 2020)
Ida Ayu Made, Wagini; This study aims to determine the inventory of raw materials in the production process to support the Martabak Alim Bengkulu City. The analytical method used was the determination of the purchase of the economy ( Economic Order Quantity ) , Inventory Safety ( Safety Stock ) , and the determination of the reorder point ( Re - Order Point . The survey results revealed that the purchase of raw materials on Martabak Alim Bengkulu City during the year 2017 with the EOQ method is 433 kg of wheat flour special for Martabak in one booking with frequency ordering as many as 4 times and intervals of 78 working days . The assessment of safety stock ( safety stock ) against wheat flour made in Martabak Alim Bengkulu City in the amount of 15 kg . appraisal ordering time again ( Re -order point) wheat flour in Martabak Alim Bengkulu City in the amount of 27 Kg . This is so that the arrival of raw materials to be booked to coincide with the current live inventory for safety stock ( safety stock ) Key Words: Analysis, Raw Material Inventory, Martabak Alim